Ethnopedagogy in Shaping the Moderate Character of Sisya Brahmacari: A Case Study in Pasraman Saraswati Tri Parartha - Wiguna, Ida Bagus Alit Arta (Institut Agama Hindu Negeri Gde Pudja Mataram, 2025)
This research examines how ethnopedagogy and culturally shaped religious moderation differ from formal education’s normative and textual approaches to religious character. Specifically, it analyzes how pasraman ethnopedagogy develops moderate character in sisya brahmacari through daily cultural practices rather than doctrinal teaching. Using a qualitative-descriptive method incorporating participatory observation, interviews, ritual documentation, and thematic analysis connected to Bourdieu's habitus theory and Geertzian cultural interpretation, the study hypothesizes that repeated cultural practice in pasraman forms moderates habitus without explicit moderation lessons. Results demonstrate that religious moderation is embodied in body ethics, emotional control, empathy, and collective rites that foster spiritual togetherness (madya), rather than delivered through direct instruction. These insights suggest that Pasraman operates as a silent but effective cultural curriculum, advancing moderate character more effectively than formal education. The article provides a model of ethnopedagogy based on cultural habits as an alternative to current moderation education, arguing for a shift from abstract principles to value internalization through lived culture.